2016
DOI: 10.4103/2231-0746.200324
|View full text |Cite
|
Sign up to set email alerts
|

Micro-marsupialization versus surgical excision for the treatment of mucoceles

Abstract: Background:Mucocele is a common disorder of minor salivary glands which arises due to mucous accumulation resulting from their alteration. Several techniques have been described for the treatment. However, most of them are invasive or require costly armamentarium.Purpose:The present study was conducted to evaluate the efficacy of micro-marsupialization technique as an alternative to surgical excision for the treatment of mucoceles.Materials and Methods:A prospective study was conducted. A total of twenty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 22 publications
0
32
2
3
Order By: Relevance
“…In the present study number of females exceeded males, however, previous published literatures do not show gender 1,6,21 predilec on.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…In the present study number of females exceeded males, however, previous published literatures do not show gender 1,6,21 predilec on.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies have shown that small 1,2,21 Mucocele a er excision have higher chance of recurrence, however, in this study there was a single case of recurrence in the pa ent who had undergone extramucosal enuclea on.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations